THEORETICAL ANALYSIS ON THE PREDICTION OF PERFORMANCE COEFFICIENT OF TWO-STAGE CASCADE REFRIGERATION SYSTEM USING VARIOUS ALTERNATIVE REFRIGERANTS - Dalkilic, Ahmet Selim (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2012)
This paper presents a comparison of the refrigerants CFC-12, HCFC-22, CFC-502, and their alternatives, such as HFC-134a, HFC-152a, HFC-404A, HFC-407C, HC-290, HC-600a, R717 (ammonia), and three mixtures composed of HFC-134a, HFC-152a, HC-600a, and HC-290. A theoretical performance study on a cascade refrigeration system was performed using two refrigeration cycles connected through a heat exchanger in the middle working as an evaporator for the high-pressure cycle and a condenser for the low-pressure cycle. The condensing temperatures varied between 40 and 60 degrees C, the evaporating temperatures varied between -50 and -10 degrees C, and the heat exchanger temperature was kept constant at 1 degrees C. The refrigerants in both cycles are assumed to be same at first. The alternative refrigerants of HFC-152a and R717 had higher coefficients of performance (COPs) than other refrigerants and also low refrigerant charge rates for all operating conditions in the case study, according to the results of the theoretical analysis. The effects of the investigated refrigerants on the depletion of the ozone layer, increase in global warming, and flammable and toxic characteristics were considered and alternative refrigerant mixtures that may be suggested were determined. It was found that refrigerant blends of HC290/HC600a (55/45 by wt%), as a non-azeotropic mixture, and HFC-152a/HFC-134a (14/86 by wt%) and HFC-134a/HC600a (82/18 by wt%), as azeotropic mixtures, gave lower performance coefficients (COPs) and required lower refrigerant charge rates than their base pure refrigerants in the analysis. The separate usage of the refrigerants R717 and HFC-152a for the high- and low-pressure sections of the cascade system, respectively, were found to be the best combination in terms of the analysis for the determination of coefficients of performance (COP) and refrigerant charge rates. The results of this study are of technological importance for efficient design when the industrial systems are assigned to utilize various alternative refrigerants.
Keywords: Refrigeration; Cascade system; R290; R600a; R152a; R717; HYDROCARBON MIXTURES; THERMODYNAMIC ANALYSIS; REPLACE HFC-134A; CFC12; Thermodynamics; Engineering